Network slicing with spectrum sharing strategy in cognitive capacity harvesting network - Jie HUANG; Fan YANG; Yingzhao XIE; Xun ZUO; Tian QIU (Tongxin xuebao)
To realizing the network slice with spectrum sharing in cognitive capacity harvesting network, a spectrum sharing strategy was proposed based on 4D conflict graph and opportunistic capacity.Firstly, a 4D conflict graph model for mesh network was built and a method to achieve the node sets with conflict free was proposed.Then, the opportunistic capacity model of spectrum sharing was established and the opportunistic capacity of the unlicensed channel was derived.Finally, the spectrum sharing strategy based on 4D conflict graph and opportunistic capacity was proposed for cognitive capacity harvesting network.The simulation results show that compared with existing algorithms, the proposed algorithm can effectively utilize opportunistic spectrum resources and further improve channel utilization.